Inhomogeneities in molecular layers of Mira atmospheres - Wittkowski, Markus; Boboltz, D. A.; Ireland, M.; Karovicova, I.; Ohnaka, K.; Scholz, Michael; Wyk, F. van; Whitelock, P.; Wood, P. R.; Zijlstra, A. A. (Astronomy and astrophysics, 2011)
Aims: We investigate the structure and shape of the photospheric and molecular layers of the atmospheres of four Mira variables. Methods: We obtained near-infrared K-band spectro-interferometric observations of the Mira variables R Cnc, X Hya, W Vel, and RW Vel with a spectral resolution of about 1500 using the AMBER instrument at the VLTI. We obtained concurrent JHKL photometry using the the Mk II instrument at the SAAO. Results: The Mira stars in our sample are found to have wavelength-dependent visibility values that are consistent with earlier low-resolution AMBER observations of S Ori and with the predictions of dynamic model atmosphere series based on self-excited pulsation models. The corresponding wavelength-dependent uniform disk (UD) diameters show a minimum near the near-continuum bandpass at 2.25 μm. They then increase by up to 30% toward the H2O band at 2.0 μm and by up to 70% at the CO bandheads between 2.29 μm and 2.48 μm. The dynamic model atmosphere series show a consistent wavelength-dependence, and their parameters such as the visual phase, effective temperature, and distances are consistent with independent estimates. The closure phases have significantly wavelength-dependent and non-zero values at all wavelengths indicating deviations from point symmetry. For example, the R Cnc closure phase is 110° ± 4° in the 2.0 μm H2O band, corresponding for instance to an additional unresolved spot contributing 3% of the total flux at a separation of ~4 mas. Conclusions: Our observations are consistent with the predictions of the latest dynamic model atmosphere series based on self-excited pulsation models. The wavelength-dependent radius variations are interpreted as the effect of molecular layers lying above the photosphere. The wavelength-dependent closure phase values are indicative of deviations from point symmetry at all wavelengths, thus a complex non-spherical stratification of the extended atmosphere. In particular, the significant deviation from point symmetry in the H2O band is interpreted as a signature on large scales (there being a few across the stellar disk) of inhomogeneities or clumps in the water vapor layer. The observed inhomogeneities might possibly be caused by pulsation- and shock-induced chaotic motion in the extended atmosphere.